ENHANCING CONTINUED INTENTION TO USE LAPERS BOT TELEGRAM THROUGH FACTORS INFLUENCING UTILITARIAN VALUE, CONFIRMATION, AND SATISFACTION - Amalia, Gina Ilma; Hidayah, Riski Taufik; Trianasari, Nurvita (Cahaya Ilmu Bangsa, 2024)
The telecommunications industry faces challenges in providing reliable applications for users. In the Customer Insight Management Division of PT Telekomunikasi Selular, the Lapers Bot Telegram is used as an alternative during U2020 maintenance, but its usage has declined significantly, indicating dissatisfaction with its performance, which could affect overall operations. This study analyzes the factors influencing employee preferences for both applications and provides recommendations to improve Lapers Bot Telegram for better effectiveness and operational efficiency. Using a quantitative approach with Partial Least Squares Structural Equation Modelling (PLS-SEM), data from 183 active Lapers Bot Telegram users was analyzed to examine variable relationships. The findings show that System Quality, Service Quality, Privacy and Security Concerns, Performance Expectancy, Facilitating Conditions, Utilitarian Value, Confirmation, Satisfaction, and Continued Intention to Use significantly influence the use of Lapers Bot Telegram, while Social Influence on Confirmation, Service Quality on Confirmation, and Information Quality on Confirmation do not. These insights help evaluate Lapers Bot Telegram’s role in supporting employee performance and guide the development of more efficient applications to enhance user satisfaction and operational effectiveness.